Development of Hybrid Electrospun Nanofibers: Improving Effects of Cellulose Nanofibers (CNFs) on Electrospinnability of Gelatin - Farnaz Hajieghrary; Babak Ghanbarzadeh; Akram Pezeshki; Saeed Dadashi; Pasquale M. Falcone (Foods, 2024)
Cellulose nanofibers (CNFs) were used to improve the electrospinnability of the gelatin protein in a water/ethanol/acetic acid (3:2:3, v/v) solution. The effects of different concentrations of CNFs (0.5–4%) on the important physical properties of the gelatin solution (15%), including rheology, conductivity, and surface tension, were investigated. The apparent viscosity and shear-thinning behavior were increased by increasing the CNF concentration from 0 to 4% at a low shear rate (<10 s−1). CNFs also increased the electrical conductivity and surface tension of the gelatin solution. Scanning electron microscopy (SEM) images revealed uniformly ordered structures with good continuity without fracture or bead formation in all hybrid nanofibers. They also showed that the average diameters of fibers decreased from 216 nm in the pure gelatin nanofibers to 175.39 nm in the hybrid gelatin/CNF (4%) ones. Differential scanning calorimetry (DSC) results showed that CNFs increased Tg, and X-ray diffraction (XRD) analysis showed that the electrospinning process caused the formation of more amorphous structures in the gelatin/CNF hybrid nanofibers. The tensile test indicated that by adding 2% CNFs, the ultimate tensile strength (UTS) and strain at break (SB) of nanofiber mats increased from 4.26 to 10.5 MPa and 3.3% to 6.25%, respectively. The current study indicated that incorporating CNFs at the optimal concentration into a gelatin solution can improve the resulting hybrid nanofibers’ morphology, average diameter, and mechanical properties.